2007
DOI: 10.1210/en.2006-0602
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Kallikrein Reverses Insulin Resistance and Attenuates Nephropathy in Diabetic Rats by Activation of Phosphatidylinositol 3-Kinase/Protein Kinase B and Adenosine 5′-Monophosphate-Activated Protein Kinase Signaling Pathways

Abstract: We previously reported that iv delivery of the human tissue kallikrein (HK) gene reduced blood pressure and plasma insulin levels in fructose-induced hypertensive rats with insulin resistance. In the current study, we evaluated the potential of a recombinant adeno-associated viral vector expressing the HK cDNA (rAAV-HK) as a sole, long-term therapy to correct insulin resistance and prevent renal damage in streptozotocin-induced type-2 diabetic rats. Administration of streptozotocin in conjunction with a high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…In contrast, low doses of dopamine and treatment with D 1 R agonists provide renal protection and have diuretic effects [48]. In addition to hypotensive effects, B 2 R stimulation by bradykinin activates MAP kinases, PI3 kinase/Akt, and JNK signaling pathways to enhance survival and reduce apoptosis [21]. rAAV-mediated delivery of the HK gene markedly upregulated B 2 R and D 1 R and downregulated AT 1 R, ET A R and V 2 R in both in vitro and in vivo experiments in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, low doses of dopamine and treatment with D 1 R agonists provide renal protection and have diuretic effects [48]. In addition to hypotensive effects, B 2 R stimulation by bradykinin activates MAP kinases, PI3 kinase/Akt, and JNK signaling pathways to enhance survival and reduce apoptosis [21]. rAAV-mediated delivery of the HK gene markedly upregulated B 2 R and D 1 R and downregulated AT 1 R, ET A R and V 2 R in both in vitro and in vivo experiments in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies documented that rAAV-HK delivery rendered a long-term and stable reduction in hypertension and provided protection against renal injury in the spontaneously hypertensive and the streptozotocin-induced type 2 diabetic rat models [12,19,21]. However, the therapeutic effect of HK on chronic renal failure has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This unique feature can render a long-term and stable expression of the target gene [4][5][6] . Previous studies have shown that a single injection of rAAV-HK gene delivery causes a prolonged reduction of systolic blood pressure in different hypertensive animal models, which makes it possible to treat hypertension through gene therapy [9,17] . However, it remains unknown whether the overexpression of the HK gene can induce hypotension in normotensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Its attenuation is suggested as a possible etiological factor in salt-sensitive hypertension [15,16] . Our previous studies have demonstrated that rAAV-HK delivery attenuates the increased blood pressure induced by fructose or streptozotocin in conjunction with a high-fat diet and ameliorates organ injury [17] . However, its effect on high-salt diet-induced hypertension in rats with normal blood pressure remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is further supported by experimental studies documenting improvement mediated by kinins of insulin resistance during ACE inhibitor treatment in obese and diabetic rodent models (Henriksen et al 1999, Shiuchi et al 2002. TK gene therapy has been reported to reverse insulin resistance and attenuate nephropathy in diabetic rats (Yuan et al 2007). Moreover, lack of kininogen or kinin B2 receptor impaired insulin sensitivity and glucose tolerance in nondiabetic animals, indicating that the KKS is involved in insulin action and glucose homeostasis (Damas et al 1999, Duka et al 2001, Kakoki et al 2010.…”
Section: Introductionmentioning
confidence: 99%